Pregunta
upstudy study bank question image url

1. Solve the pairs of simultaneous equations. a) \( x+y=5 ; \quad x-y=3 \) b) \( x-3 y=-5 ; \quad 2 x+3 y=-1 \) c) \( 2 x-3 y=-21 ; \quad 2 x+3 y=1 \) c)

Ask by Schultz Rodriguez. in South Africa
Feb 19,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions to the pairs of simultaneous equations are: a) \( x = 4, y = 1 \) b) \( x = -2, y = 1 \) c) \( x = -5, y = \frac{11}{3} \)

Solución

Solve the equation \( x+y=5;x-y=3 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y=5\\x-y=3\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=5-y\\x-y=3\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5-y-y=3\) - step3: Subtract the terms: \(5-2y=3\) - step4: Move the constant to the right side: \(-2y=3-5\) - step5: Subtract the numbers: \(-2y=-2\) - step6: Change the signs: \(2y=2\) - step7: Divide both sides: \(\frac{2y}{2}=\frac{2}{2}\) - step8: Divide the numbers: \(y=1\) - step9: Substitute the value of \(y:\) \(x=5-1\) - step10: Calculate: \(x=4\) - step11: Calculate: \(\left\{ \begin{array}{l}x=4\\y=1\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=4\\y=1\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(4,1\right)\) Solve the equation \( x-3y=-5;2x+3y=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x-3y=-5\\2x+3y=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-5+3y\\2x+3y=-1\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\left(-5+3y\right)+3y=-1\) - step3: Simplify: \(-10+9y=-1\) - step4: Move the constant to the right side: \(9y=-1+10\) - step5: Add the numbers: \(9y=9\) - step6: Divide both sides: \(\frac{9y}{9}=\frac{9}{9}\) - step7: Divide the numbers: \(y=1\) - step8: Substitute the value of \(y:\) \(x=-5+3\times 1\) - step9: Substitute back: \(x=-5+3\) - step10: Calculate: \(x=-2\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-2,1\right)\) Solve the equation \( 2x-3y=-21;2x+3y=1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-3y=-21\\2x+3y=1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{-21+3y}{2}\\2x+3y=1\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\times \frac{-21+3y}{2}+3y=1\) - step3: Simplify: \(-21+6y=1\) - step4: Move the constant to the right side: \(6y=1+21\) - step5: Add the numbers: \(6y=22\) - step6: Divide both sides: \(\frac{6y}{6}=\frac{22}{6}\) - step7: Divide the numbers: \(y=\frac{11}{3}\) - step8: Substitute the value of \(y:\) \(x=\frac{-21+3\times \frac{11}{3}}{2}\) - step9: Calculate: \(x=-5\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=\frac{11}{3}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=\frac{11}{3}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-5,\frac{11}{3}\right)\) The solutions to the pairs of simultaneous equations are: a) \( x = 4, y = 1 \) b) \( x = -2, y = 1 \) c) \( x = -5, y = \frac{11}{3} \) or \( x = -5, y = 3.6 \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equations, let's break it down step by step! For a) 1. From the first equation \( x + y = 5 \), we can express \( y \) as \( y = 5 - x \). 2. Substituting into the second equation \( x - (5 - x) = 3 \) gives us \( 2x - 5 = 3 \), leading to \( 2x = 8 \) or \( x = 4 \). 3. Plugging \( x = 4 \) back into \( y = 5 - x \), we find \( y = 1 \). **Solution: \( (4, 1) \)** For b) 1. Rearranging the first equation \( x - 3y = -5 \) gives us \( x = 3y - 5 \). 2. Substitute into the second equation: \( 2(3y - 5) + 3y = -1 \) simplifies to \( 6y - 10 + 3y = -1 \). 3. This leads to \( 9y - 10 = -1 \), so \( 9y = 9 \) or \( y = 1 \). 4. Plugging back, \( x = 3(1) - 5 = -2 \). **Solution: \( (-2, 1) \)** For c) 1. From \( 2x - 3y = -21 \), we can express \( 2x = -21 + 3y \) or \( x = \frac{-21 + 3y}{2} \). 2. Plug this expression into the second equation \( 2\left(\frac{-21 + 3y}{2}\right) + 3y = 1 \) which simplifies to \( -21 + 3y + 3y = 1 \). 3. Thus, \( 6y - 21 = 1 \) leads to \( 6y = 22 \) or \( y = \frac{11}{3} \). 4. Substituting this back, \( 2x - 3\left(\frac{11}{3}\right) = -21 \) leads us to \( 2x - 11 = -21 \) or \( 2x = -10 \) hence \( x = -5 \). **Solution: \( (-5, \frac{11}{3}) \)**

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad